Multimodal 2D+3D face recognition - I Gede Putra Kusuma Negara (2012)
The growing interest in face recognition is fueled by its potential applications in commercial and law enforcement. Although humans seem to have an innate ability to recognize and distinguish between faces, computerized face recognition systems have not yet been able to achieve satisfactory performances. The worldwide implementation of face recognition has been hindered by its inherent problems. The appearance of a face may vary significantly due to variations in illumination condition, head pose, and facial expression, to name a few. On the other hand, faces basically belong to the same class of objects. They consist of the same facial features in the same geometrical configuration. When all other factors are held constant, faces of different persons are somewhat similar and the differences between them can be quite subtle.